Unified constant-frequency integration control of active power filters-steady-state and dynamics. - Smedley, K.M (IEEE Transactions on power electronics)
An active power filter (APF) is a device that is connected in parallel to and cancels the reactive and harmonic currents from a group of nonlinear loads so that the resulting total current drawn from the AC mains is sinusoidal. This paper presents a unified constant-frequency integration (UCI) APF control method based on one-cycle control. This method employs an integrator with reset as its core component to control the pulse width of an AC-DC converter so that its current draw is precisely opposite to the reactive and harmonic current draw of the nonlinear loads. In contrast to previously proposed methods, there is no need to generate a current reference for the control of the converter current, thus no need for a multiplier and no need to sense the AC line voltage, the APF current, or the nonlinear load current. Only one AC current sensor is used to sense the AC main current and one DC voltage sensor is used to sense the DC capacitor voltage. The control method features constant switching frequency operation, minimum reactive and harmonic current generation, and simple analog circuitry. It provides a low cost and high performance solution for power quality control. Steady-state and dynamic study is presented in this paper. Design example is given using a two-level AC-DC boost topology. A prototype was developed to demonstrate the performance of the proposed APF. This control method is generalized to control a family of converters that are suitable for APF applications. All findings are supported by experiments and simulation